Spontaneous perforation of the cystic duct in an infant - Workye Tigabie; Goytom Knfe Tesfay; Yeneneh Yirga (Elsevier, 2022)
Introduction: Spontaneous perforation of the biliary tract (SPBT) is an exceedingly rare cause of peritonitis that it is rarely diagnosed preoperatively. With only a few cases of perforation of the cystic duct reported worldwide previously, this is likely to be the first reported case from Ethiopia. Case presentation: Here we present a case of spontaneous cystic duct perforation in 51 days old male infant who presented with a complaint of failure to pass feces and flatus and abdominal distension of 1-day duration associated with three episodes of non-projectile vomiting of bilious matter, and high-grade fever of the same duration. Signs of peritonitis were found upon examination. He was taken up for laparotomy, and a diagnosis of biliary peritonitis secondary to spontaneous cystic duct perforation was made intra-operatively. The patient recovered well after lavage and cholecystectomy and was discharged improved on postoperative day 5. Discussion: Spontaneous perforation of the biliary tract is a disease entity in which the wall of the extrahepatic or intrahepatic duct is perforated without any traumatic or iatrogenic injury. The exact etiopathogenesis of SPBT is unknown but there are proposed speculative mechanisms. The classic presentation is that of a previously healthy infant who develops progressive ascites and abdominal distension, irritability, and fluctuating mild jaundice. Although the treatment is not well established, surgical intervention has a definitive role ranging from percutaneous tube placement to complicated biliary procedures. Conclusion: The spontaneous perforation of the biliary tract is a disease that represents a diagnostic challenge due to its low frequency and nonspecific symptoms. Nevertheless, SPBT should be considered as a differential diagnosis in healthy infants being examined for abdominal distension, ascites, and history of fluctuating jaundice as early diagnosis and prompt surgical intervention greatly reduce morbidity and mortality from the disease.